Partial revision of the genus Robinsonia Grote 1866: description of five new species for the Neotropical fauna (Lepidoptera, Erebidae, Arctiinae, Phaegopterina) - Laguerre, Michel (Zootaxa, 2021)
The genus Robinsonia Grote, 1866 is partially reviewed following a large DNA barcode campaign. In the Robinsonia praphoea Dognin, 1906 group three new species are described: R. simulans sp. n. from French Guiana, up to now confused with R. praphoea itself and then R. decaensi sp. n. and R. maranhensis sp. n. both from the lower Amazon. R. drechseli sp. n. is described from Paraguay and R. inexpectata sp. n., a species close to R. mera (Schaus, 1910) from Costa Rica, is described as new from Peru and Bolivia. Finally the full species status is confirmed for R. flavicorpus Dognin, 1910 which is found to be differentiable from R. marginata Rothschild, 1909. All types are figured along with the male genitalia for most and some female genitalia for all studied species.